Cell-specific activation of RIPK1 and MLKL after intracerebral hemorrhage in mice. Issue 7 (July 2021) - Lule, Sevda; Wu, Limin; Sarro-Schwartz, Aliyah; Edmiston, William J; Izzy, Saef; Songtachalert, Tanya; Ahn, So Hee; Fernandes, Neil D; Jin, Gina; Chung, Joon Yong; Balachandran, Siddharth; Lo, Eng H; et al.
Receptor-interacting protein kinase-1 (RIPK1) is a master regulator of cell death and inflammation, and mediates programmed necrosis (necroptosis) via mixed-lineage kinase like (MLKL) protein. Prior studies in experimental intracerebral hemorrhage (ICH) implicated RIPK1 in the pathogenesis of neuronal death and cognitive outcome, but the relevant cell types involved and potential role of necroptosis remain unexplored. In mice subjected to autologous blood ICH, early RIPK1 activation was observed in neurons, endothelium and pericytes, but not in astrocytes. MLKL activation was detected in astrocytes and neurons but not endothelium or pericytes. Compared with WT controls, RIPK1 kinase-dead ( RIPK1 D138N/D138N ) mice had reduced brain edema (24 h) and blood-brain barrier (BBB) permeability (24 h, 30 d), and improved postinjury rotarod performance. Mice deficient in MLKL ( Mlkl -/- ) had reduced neuronal death (24 h) and BBB permeability at 24 h but not 30d, and improved post-injury rotarod performance vs. WT. The data support a central role for RIPK1 in the pathogenesis of ICH, including cell death, edema, BBB permeability, and motor deficits. These effects may be mediated in part through the activation of MLKL-dependent necroptosis in neurons. The data support development of RIPK1 kinase inhibitors as therapeutic agents for human ICH.